Tindak Tutur Perlokusi dalam Tuturan Penjual dan Pembeli Bawang Merah di Pasar Randudongkal - Solihatun, Iha; Sunarya, Sunarya; Werdiningsih, Yuli Kurniati (Universitas PGRI Semarang, 2022)
The purpose of writing this paper is to describe the speech acts of perlocution in speech between the seller and buyer of vegetables in the Randudongkal market. The method used to describe the speech acts of perlocution in this speech is descriptive qualitative. The research technique used is in the form of competent free listening, note-taking, and recording techniques. Research data in the form of words, phrases, and sentences that contain acts of speech in the discussion between the seller and buyer of vegetables. The theory used is the pragmatic theory with a focus on speech acts of percussion in speech. There are four types of findings of speech actuality in speech between the seller and buyer of vegetables in the Rndudongkal market, namely representative is a speech act that states a truth, a directive is a speech act that states an order, a commissive act is a speech act that states a commitment, and expressive are a speech act that expresses psychological action. The results of this study indicate that the act of perlocutionary speech that is often used by sellers and buyers of vegetables in the Randudongkal market is the type of directive actuation perlocution, especially the type of demand.